Cationic liposomes promote antigen cross-presentation in dendritic cells by alkalizing the lysosomal pH and limiting the degradation of antigens - Gao J; Ochyl LJ; Yang E; Moon JJ (International Journal of Nanomedicine, 2017)
Jie Gao,1–3 Lukasz J Ochyl,1,3 Ellen Yang,4 James J Moon1,3,5 1Department of Pharmaceutical Sciences, University of Michigan, Ann Arbor, MI, USA; 2Department of Pharmaceutical Sciences, School of Pharmacy, Second Military Medical University, Shanghai, People’s Republic of China; 3Biointerfaces Institute, 4Department of Chemistry, 5Department of Biomedical Engineering, University of Michigan, Ann Arbor, MI, USA Abstract: Cationic liposomes (CLs) have been widely examined as vaccine delivery nanoparticles since they can form complexes with biomacromolecules, promote delivery of antigens and adjuvant molecules to antigen-presenting cells (APCs), and mediate cellular uptake of vaccine components. CLs are also known to trigger antigen cross-presentation – the process by which APCs internalize extracellular protein antigens, degrade them into minimal CD8+ T-cell epitopes, and present them in the context of major histocompatibility complex-I (MHC-I). However, the precise mechanisms behind CL-mediated induction of cross-presentation and cross-priming of CD8+ T-cells remain to be elucidated. In this study, we have developed two distinct CL systems and examined their impact on the lysosomal pH in dendritic cells (DCs), antigen degradation, and presentation of peptide:MHC-I complexes to antigen-specific CD8+ T-cells. To achieve this, we have used 3β-[N-(N',N'-dimethylaminoethane)-carbamoyl] cholesterol (DC-Chol) and 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP) as the prototypical components of CLs with tertiary amine groups and compared the effect of CLs and anionic liposomes on lysosomal pH, antigen degradation, and cross-presentation by DCs. Our results showed that CLs, but not anionic liposomes, elevated the lysosomal pH in DCs and reduced antigen degradation, thereby promoting cross-presentation and cross-priming of CD8+ T-cell responses. These studies shed new light on CL-mediated cross-presentation and suggest that intracellular fate of vaccine components and subsequent immunological responses can be controlled by rational design of nanomaterials. Keywords: cationic liposome, nanoparticle, vaccine, cross-presentation, lysosome